Analysis of predisposing factors affecting community antibiotic use behavior in Mampang Village Depok City - Sherly Tandi Arrang; Najwa Arumiyati Abella; Hadiyanto; Evi Ulina Margareta (JURNAL ILMU KEFARMASIAN INDONESIA, 2026)
Antibiotic misuse remains prevalent in Indonesia, including behaviors such as storing antibiotics and using them without a doctor's prescription. Despite this widespread issue, no prior studies have specifically examined antibiotic use behavior in Mampang Village in Depok City. This study aimed to analyze the relationship between predisposing factors, namely age, sex, education level, occupation, and knowledge level and antibiotic use behavior among the local population. An analytical observational design with a cross-sectional approach was applied to 110 respondents. Knowledge levels were assessed using a structured questionnaire, and the relationships between predisposing factors and behavior were analyzed using multivariate logistic regression. The findings revealed that the majority of respondents had good knowledge (43%) and exhibited appropriate antibiotic-use behavior (52%). Statistical analysis indicated a significant association between knowledge and antibiotic use behavior (p < 0.001). In contrast, age (p = 0.166), sex (p = 0.938), education level (p = 0.340), and occupation (p = 0.365) were not significantly associated with the knowledge score. These results suggest that knowledge is a key predisposing factor influencing antibiotic use behavior in the Mampang Village community.